Diameter dependence of single-walled carbon nanotubes with flavin adenine dinucleotide glucose dehydrogenase for direct electron transfer bioanodes. (1st May 2019) - Suzuki, Atsuya; Ishida, Kazuya; Muguruma, Hitoshi; Iwasa, Hisanori; Tanaka, Takeshi; Hiratsuka, Atsunori; Tsuji, Katsumi; Kishimoto, Takahide
Abstract: The diameter dependence of single-walled carbon nanotubes (SWCNTs) with flavin adenine dinucleotide glucose dehydrogenase (FAD-GDH) for direct electron transfer (DET) type bioanodes is presented for the first time. In order to address the issue, we use SWCNTs having different diameters fabricated by direct-injection pyrolytic synthesis, which can control the diameter in a wide range with the other parameters fixed. Three different diameters of SWCNTs are examined: average diameter d m = 1.0, 1.5, and 2.0 nm. In order to achieve DET, a debundled, individual SWCNT has to be placed at the FAD position in the GDH protein pocket. The bioanodes with d m = 1.0 and 1.5 nm SWCNTs show better performance than that with d m = 2.0 nm SWCNTs. The diameter dependence of SWCNTs for bioanode performance is thought to be related to the distance between the SWCNTs and FAD positioned in the reaction center of the GDH protein shell.